2019
DOI: 10.3892/mmr.2019.10177
|View full text |Cite
|
Sign up to set email alerts
|

Pressure suppresses hepatocellular glycogen synthesis through activating the p53/Pten pathway

Abstract: Portal hypertension is the primary cause of complications in patients with chronic liver diseases, and markedly impacts metabolism within the nervous system. Until recently, the role of portal hypertension in hepatocellular metabolism was unclear. The present study demonstrated that an increase in extracellular pressure significantly decreased hepatocellular glycogen concentrations in HepG2 and HL-7702 cells. In addition, it reduced glycogen synthase activity, by inhibiting the phosphorylation of glycogen synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…The 2-dimensional (2D) pressure loading system was designed and manufactured by our research group, and the protocol can be found in our previous papers [14,29,30]. The Flexcell-5000 Compression System (Flexcell International Corp, Burlington, NC, US) was used to exert pressure on the 3D cultured cells.…”
Section: Pressure Loadingmentioning
confidence: 99%
“…The 2-dimensional (2D) pressure loading system was designed and manufactured by our research group, and the protocol can be found in our previous papers [14,29,30]. The Flexcell-5000 Compression System (Flexcell International Corp, Burlington, NC, US) was used to exert pressure on the 3D cultured cells.…”
Section: Pressure Loadingmentioning
confidence: 99%